The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/life13041065
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Assist Device as a Destination Therapy: Current Situation and the Importance of Patient Selection

Abstract: Advanced heart failure is a growing problem for which the best treatment is cardiac transplantation. However, the shortage of donors’ hearts made left ventricular assist devices as destination therapy (DT-LVAD) a highly recommended alternative: they improved mid-term prognosis as well as patients’ quality of life. Current intracorporeal pumps with a centrifugal continuous flow evolved in the last few years. Since 2003, when first LVAD was approved for long-term support, smaller device sizes with better surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The 2022 INTERMACS registry also demonstrated an increased proportion of DT from 50.4% (2012–2016) to 66.4% (2017–2021), while the BTT proportion has declined from 27.5% to 19.5%. Although BTT has better survival rates due to younger age and fewer comorbidities compared to DT, 1-year survival in DT is still acceptable (77%) [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2022 INTERMACS registry also demonstrated an increased proportion of DT from 50.4% (2012–2016) to 66.4% (2017–2021), while the BTT proportion has declined from 27.5% to 19.5%. Although BTT has better survival rates due to younger age and fewer comorbidities compared to DT, 1-year survival in DT is still acceptable (77%) [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the standard exclusion criteria for LVADs and HTs in patients with advanced heart failure is multi-system organ dysfunction 17 . However, recent studies have shown that LVADs may be performed in patients with severe renal insufficiency without an increase in mortality and morbidity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that LVADs may be performed in patients with severe renal insufficiency without an increase in mortality and morbidity 18 . Similarly, liver cirrhosis is no longer a formal contraindication, and select patients can qualify for LVAD, but 'irreversible liver damage' is still considered a contraindication 17 . Interestingly, our study noted that the highest use of LVADs was with multiorgan failure and single organ failure as compared to no organ failure in both the non-AMI CS group and the all-CS group.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of valve disease is also considered, with severe mitral stenosis and mild aortic regurgitation classified as contraindications. A neurological and cognitive assessment will also be conducted, since moderate-severe cognitive impairment and dementia are contraindications for MCS [25]. Together, these considerations enable healthcare providers to make informed decisions regarding patient suitability for device implantation, aiming to improve patient care.…”
Section: Complications In Mcs 21 Patient Selection and Challenges In ...mentioning
confidence: 99%